Pengaruh Fraksi Massa Serat Terhadap Kekuatan Fatik Material Komposit Berpenguat Serat Tandan Kosong Kelapa Sawit - Devi Chandra; Randha Mulia; Dedison Gasni; Gusriwandi Gusriwandi (Department of Mechanical Engineering, Universitas Andalas, 2018)
The present study was investigated the effect of fiber mass fraction on the tensile and fatigue strength of oil palm fiber reinforced composite and resin as the matrix. Fatigue test has been performed by using rotary bending fatigue machine. The specimens were made by press hand lay-up with matrix to fiber mass ratio was 90:10, 80:20 and 70:30 respectively. Fracture surface of fatigue specimens have also been observed by using digital camera to knowing the failure mode. The results showed that the tensile and fatigue strength and fatigue life increased with increasing the fiber mass fraction as seen in the S-N curve. The fatigue limit was found 0.27 MPa, 0.55 MPa, and 0.82 MPa for composites with 90:10, 80:20 and 70:30 of matrix to fiber mass ratio respectively. The observed failure modes were matrix cracking, fiber debonding, and fiber breaking.